Level of awareness towards brand equity among Malay entrepreneurs in food industry in Terengganu / Muhammad Abi Sofian Abd Halim, Wan Asri Wan Ab Aziz and Zainuddin Zakaria - Abd Halim, Muhammad Abi Sofian; Wan Ab Aziz, Wan Asri; Zakaria, Zainuddin (2008)
Today, most of local entrepreneurs who are involved in small and medium industry (SMI) have encouraged producing a quality product to fulfill the consumer requirement. Entrepreneurs also have to know a new trend in product development like a promotion, packaging, labeling and branding. Government has already highlighted these things into the policies and implemented to help local entrepreneur to become more confidence in the marketplace, especially for those who want to market their product into foreign hypermarket. Yayasan Pembangunan Usahawan Terengganu is one of the government agencies under Ministry of Entrepreneurs and Co-operation Development (MECD) that responsible in these things for entrepreneur development in Terengganu. Nowadays, Yayasan Pembangunan Usahawan Terengganu more emphasis to develop brand awareness among Malay entrepreneurs for those who are involved in food industry. Meanwhile, many other competitors in food industry which established their products are now moving forward to maintaining their image, to meet the challenges of market liberalization and increasing competition for both domestic and international market. But, how many of our local entrepreneurs are aware to plan and implement their brand development